ANGKA KEJADIAN, LENGTH OF STAY, DAN MORTALITAS PASIEN ACUTE KIDNEY INJURY DI ICU RSUP DR. HASAN SADIKIN TAHUN 2018 - Hidayat Hidayat; Erwin Pradian; Nurita Dian Kestriani (Faculty of Medicine, Universitas Padjadjaran, 2020)
Angka kejadian acute kidney injury (AKI) di ICU tergolong tinggi dengan penyebab utama adalah sepsis dan menjadi salah satu faktor yang memengaruhi lama rawat dan mortalitas pasien di ICU. Angka kejadian, lama rawat, dan mortalitas AKI pada ICU di Indonesia belum diketahui. Tujuan penelitian ini mengetahui angka kejadian AKI, lama rawat dan mortalitas pasien AKI di ICU RSUP dr Hasan Sadikin pada tahun 2018. Penelitian ini merupakan penelitian deskriptif yang dilakukan pada 148 pasien yang dirawat di ICU RSUP dr. Hasan Sadikin Tahun 2018. Diagnosis AKI ditentukan melalui kriteria KDIGO dengan melihat peningkatan kreatinin serum dan penilaian urine output. Penelitian ini dilakukan mulai September 2019 sampai Februari 2020. Pada penelitian ini diperoleh sebanyak 61 pasien (41,2%) dengan diagnosis AKI, mayoritas pasien didiagnosis AKI tahap 3 yaitu sebanyak 32 pasien (53%). Sebanyak 14,8% pasien mendapatkan renal replacement therapy (RRT. Rerata lama rawat pada pasien AKI di ICU, yaitu 9,4±7,2 hari dan mortalitas sebesar 77%. Simpulan, angka kejadian AKI di ICU RSUP Dr. Hasan Sadikin Bandung tergolong tinggi, yaitu 41,2% serta mortalitas yang juga tinggi, yaitu 77%. Frequency, Length of Stay, And Mortality of Patients with Acute Kidney Injury at ICU Dr. Hasan Sadikin Hospital BandungIncidence of acute kidney injury (AKI) among patients treated in Intensive Care Units (ICU) is relatively high, mainly due to sepsis. The presence of AKI affects the patient’s length of stay (LOS) in the ICU as well as the mortality of ICU patients. In Indonesia, no data is available for the incidence of AKI in ICUs and the LOS and mortality rate of ICU patients with AKI. This study aimed to determine AKI incidence in ICU patients and the length of stay and mortality rate of ICU patients with AKI in Dr. Hasan Sadikin General Hospital in 2018. This was a descriptive study conducted on 148 patients treated at the ICU of Dr. Hasan Sadikin General Hospital 2018. The diagnosis of AKI was confirmed using the Kidney Disease Improving Global Outcomes (KDIGO) criteria by observing the increase in creatinine serum and assessing the urine output. Data were collected during the period of September 2019 to February 2020 for analysis. Results showed that among 61 patients (41.2%) diagnosed with AKI, the majority were diagnosed with stage 3 AKI (n=32; 52.5%). A total of 14.8% of patients received RRT therapy. The mean LOS of AKI patients in ICU was 9.4±7.2 days and the mortality rate was 77%. Thus, the incidence of AKI in the ICU of Dr. Hasan Sadikin General Hospital is relatively high (41.2%) with a high mortality rate (77%).